Factors associated with perception of disorder with water and restriction among patients with chronic renal failture - da Silva Oliveira, Eliardo (2020)
The study aimed to analyze the perception of discomfort in the face of water and food restrictions by people with chronic renal failure. This was a cross-sectional study with an intentional sample of 207 hemodialysis therapy users from a hospital in Bahia's Alto Sertão, Brazil. Data were collected between September and October 2018 by applying a clinic and sociodemographic form and Kidney Disease Quality of Life (KDQOL-SF). Descriptive and association analyzes were performed (p <0.05) by Pearson's chi-square test. It was found that 75.9% of users reported discomfort with water restriction, while 56.5% indicated discomfort with decreased diet. Being of productive age (p = 0.040), receiving continued benefit (p = 0.027) and being hypertensive (p = 0.006) was associated with the discomfort caused by water restriction. Race / black color (p = 0.047) was associated with discomfort with food restriction. The users of hemodialysis therapy bothered by water and food restriction presented different sociodemographic profiles, which directly impacted the quality of life of the affected and professional actions.